Tingkat Infeksi Ektoparasit Protozoa pada Benih Ikan Nila (Oreochromis niloticus) di Balai Benih Ikan (BBI) Pandak dan di Balai Benih Ikan (BBI) Sidabowa Kabupaten Banyumas - Mulia, Dini Siswani (Sain Akuatik, 2007)
The aims of this research was to know prevalency of protozoa ectoparasites in fish fry of nila (Oreochromis niloticus). Experiments held at two different ponds, Local Hatchery Center (BBI) Pandak and Local Hatchery Center (BBI) Sidabowa, Banyumas regency. The research method used survey and the location site was determined with purposive sampling method. The samples were taken randomly (random sampling) from two locations. Total fishes samples were 135, as follow 75 of fishes from BBI Pandak and other 60 fishes from BBI Sidabowa, with twice replication of taking samples.  The datas was analyzed descriptively and continued with t test to compare the prevalency of ectoparasite in   Pandak and  Sidabowa. The result of this research showed the type of ectoparasite and infection level that nila fish fry at Pandak which found in the surface and gill were Trichodina sp. (80% & 18,67%), Ichtyophthirius multifiliis (58,67% & 24%), Chilodonella sp. (29,33% & 5,33%), Epistylis sp. (49,33% & 0%), Vorticella sp. (15% & 0%), while type of ectoparasite and infection level which found in the surface and gill at Sidabowa were Trichodina sp. (86,67% & 63,33%), Ichtyophthirius multifiliis (53,33% & 23,33%), Chilodonella sp. (18,33% & 3,33%), Epistylis sp. (23,33% & 0%). The t test compare the prevalency showed inexistence differences of ectoparasite infection level (P>0,05) between Pandak and Sidabowa.